Peningkatan Nilai Tambah Kopi Melalui Inovasi Produk Berbasis Olahan Kopi Kreatif - Dwimahendrawan , Andrias; Maharani , Ivana Septia; Rofi , Ahmad (LPPM Universitas PGRI Argopuro Jember, 2026)
The Program for Increasing Coffee Value Added through Creative Coffee-Based Product Innovation represents a strategic effort to strengthen the local economy based on regional flagship commodities. To date, coffee has predominantly been marketed in the form of raw materials or primary processed products, resulting in relatively low value added for farmers and business actors. Through the development of innovative creative coffee-based processed products, this program aims to enhance economic value, product competitiveness, and the sustainability of coffee-related enterprises. The activities focus on improving human resource capacity through training in processing technology, packaging, and quality standardization. The resulting product innovations are expected to expand market segmentation and increase community income. Thus, this program contributes to sustainable local economic development by optimizing local potential and promoting community welfare.